Teaching Digital Business: Integrating Digital Business Materials into English Language Teaching (ELT) - Fitria, Tira Nur (ITB AAS Indonesia Surakarta, 2024)
This research describes the integration of digital business materials into English Language Teaching (ELT). This research is descriptive qualitative research. The analysis shows that English proficiency is fundamental for adapting and succeeding in digital business amid ongoing globalization and technological advancement. Integrating digital business contexts into English materials equips learners with technical terms and concepts essential for innovation and management in digital enterprises. Teaching English skills for digital business is crucial for preparing individuals to thrive in today's interconnected global business landscape. Teaching English for digital business requires an integrated approach focused on e-commerce, digital marketing, and fintech contexts. Proficiency in English facilitates effective communication via digital platforms like email, video conferencing, and social media, enabling seamless collaboration with international colleagues and clients. It also ensures direct access to essential information and documentation in English within a digital business, eliminating translation barriers and ensuring comprehensive understanding. Mastery of English in understanding technology concepts such as e-commerce and artificial intelligence empowers individuals to actively contribute to strategic decision-making. In digital marketing, English proficiency is vital for creating compelling content and optimizing strategies globally. Teaching materials for English language skills in digital business cover a broad spectrum of topics in reading, writing, listening, and speaking. These include analyzing case studies of digital transformations, reading industry whitepapers on blockchain and e-commerce trends, understanding regulatory documents, and analyzing big data for consumer insights. Writing tasks range from crafting technology project proposals to developing SEO-driven content strategies and drafting legal contracts. Listening activities involve industry podcasts, negotiation simulations, and webinars on technology innovations while speaking exercises include pitching ideas, cross-cultural communication, and presenting digital products. These materials not only enhance language proficiency but also cultivate analytical, communication, and strategic skills essential for navigating the complexities of the digital economy and seizing global business opportunities.